Tem evento na cidade: o festival folclórico e as transformações urbanas em Parintins - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
This study deals with the urban transformations in Parintins resulting from the Folkloric Festival that takes place in this city, as an expression of the relationship between city and event. The period from 1988 to 2018 is cut out. Specifically, we tried to understand how the Parintins Folk Festival influences the transformations of the city, as well as the changes that it induces in the urban dynamics, in view of the architectural marks of this event when it is spatialized in the city. It was assumed that the Parintins Folk Festival event, from 1988 to 2018, produced changes in the city that influenced the urban structure in Parintins. We also sought to assess what are the characteristics and uses of urban public spaces resulting from the spatialization of the Festival itself. It is noteworthy that the reading of urban public space went beyond the morphological analysis, in that the understanding about the experience of these spaces was also taken into account from the sociability. The methodology was based on an ethnographic approach to compose a descriptive and analytical study, using instruments such as bibliographic, documentary research, participant observation, semi structured interviews and field diary.
Keywords: Festas folclóricas - Parintins (AM); Bumba-meu-boi - Parintins (AM); Parintins (AM) - Edifícios, estruturas, etc.; Espaços públicos - Parintins (AM); Sociologia urbana; CIENCIAS HUMANAS; Cidade de Parintins; Festival Folclórico de Parintins; Transformações urbanas; Espaço público; Sociabilidade urbana